2016
DOI: 10.1002/2015ja022333
|View full text |Cite
|
Sign up to set email alerts
|

Four‐fluid MHD simulations of the plasma and neutral gas environment of comet 67P/Churyumov‐Gerasimenko near perihelion

Abstract: The neutral and plasma environment is critical in understanding the interaction of the solar wind and comet 67P/Churyumov‐Gerasimenko (CG), the target of the European Space Agency's Rosetta mission. To serve this need and support the Rosetta mission, we have developed a 3‐D four‐fluid model, which is based on BATS‐R‐US (Block‐Adaptive Tree Solarwind Roe‐type Upwind Scheme) within SWMF (Space Weather Modeling Framework) that solves the governing multifluid MHD equations and the Euler equations for the neutral g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 50 publications
(74 reference statements)
3
40
0
Order By: Relevance
“…We point out here that R * primarily follows the (reciprocal of the) neutral density, which in turn largely varies in response to changes in the spacecraft latitude, shown in Figure 5e (black line), as a consequence of the seasonal variations in outgassing over the comet nucleus. We also note that the conspicuous lack of cavity events at small R * around the turn of the months August-September and October-November can possibly be explained by the low solar zenith angle (also known as phase angle), shown in Figure 5e (red line) at these times; the extent of the cavity is expected to be smaller closer to the Sun-comet line (Huang et al, 2016;Koenders et al, 2015). Figure 5f shows the total H 2 O production rate model by Hansen et al (2016, black line) and the local production rate calculated as 4 n n r 2 ⋅ u, for a neutral outflow velocity u of 1 km/s (gray dots).…”
Section: Statistical Survey Of All Cavity Crossingsmentioning
confidence: 80%
“…We point out here that R * primarily follows the (reciprocal of the) neutral density, which in turn largely varies in response to changes in the spacecraft latitude, shown in Figure 5e (black line), as a consequence of the seasonal variations in outgassing over the comet nucleus. We also note that the conspicuous lack of cavity events at small R * around the turn of the months August-September and October-November can possibly be explained by the low solar zenith angle (also known as phase angle), shown in Figure 5e (red line) at these times; the extent of the cavity is expected to be smaller closer to the Sun-comet line (Huang et al, 2016;Koenders et al, 2015). Figure 5f shows the total H 2 O production rate model by Hansen et al (2016, black line) and the local production rate calculated as 4 n n r 2 ⋅ u, for a neutral outflow velocity u of 1 km/s (gray dots).…”
Section: Statistical Survey Of All Cavity Crossingsmentioning
confidence: 80%
“…They find that the distance to the nucleus is about 50 100 km depending on the phase angle, the angle between Sun-comet line and the spacecraft comet line. Four-fluid simulations presented in Huang et al (2016) show that with an asymmetric outgassing profile the cavity extends to 100 km. Goetz et al (2016) reported that the extension of the cavity was much larger than theoretically expected, based on the analysis of magnetic field data during one cavity detection on July 26, 2015.…”
Section: Introductionmentioning
confidence: 98%
“…Similar effects are expected at comet 67P. Recently, Huang et al (2016) used a four-fluid MHD model to investigate the effect of a more realistic nucleus illumination model on comet 67P's plasma environment at perihelion. They find a bow shock standoff distance increasing from 6000 km to 10 000 km when including an asymmetric gas outflow, suggesting that an equivalent higher outgassing rate in a symmetric Haser neutral model should be used to account for the increase in neutral density on the subsolar side.…”
Section: Limitationsmentioning
confidence: 69%
“…This would substantially increase the neutral atmosphere and plasma interaction region, likely expanding the cometopause in the direction of the subsolar point, with cometary ions becoming the major species at larger cometocentric distances and possibly at the maximum distance of Rosetta's excursion. The effect of an illumination-driven model of the cometary neutral outgassing should also increase the bow shock distance substantially, as shown by Huang et al (2016) with their multi-fluid MHD model.…”
Section: Discussion In the Context Of Rosettamentioning
confidence: 87%
See 1 more Smart Citation